Protective Effects of Rocuronium Bromide on Ischemia-Reperfusion Injury in Skeletal Muscle Induced by Tourniquet in Patients Undergoing Elective Unilateral Total Knee Arthroplasty: A Prospective, Double Blind, Randomized, Controlled Study - Chen H; Wei JQ; Wang YW; Zhou KP; He Y; Liu H; Zhang YY (Dove Medical Press, 2020)
Hui Chen,* Jing-Qiu Wei,* Yi-Wen Wang, Kun-Peng Zhou, Ying He, He Liu, Yue-Ying Zhang Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu 221004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yue-Ying Zhang Department of AnesthesiologyThe Affiliated Hospital of Xuzhou Medical University, Huaihai Western Road, Quanshan District, Xuzhou, Jiangsu 221004, People’s Republic of ChinaTel +86 138 1531 0789Email zyy0218@126.comPurpose: To investigate the effects of different doses of rocuronium on ischemia-reperfusion injury in skeletal muscle induced by tourniquet in patients undergoing elective unilateral total knee arthroplasty.Patients and Methods: A total of 90 patients undergoing elective unilateral knee arthroplasty under general anesthesia combined with femoral nerve block were randomly divided into 3 groups: normal saline group (group S), rocuronium 0.6 mg/kg group (group L), and rocuronium 1.2 mg/kg group (group H). The primary outcome was the expression of dystrophin in skeletal muscle at 60 min after ischemia. Secondary outcomes included the concentration of malondialdehyde (MDA) and neuronal nitric oxide synthase (nNOS) in blood at 5 min and 30 min after reperfusion. In addition, thigh girth at 24 h and 48 h after operation, the leaving bed time, the incidence of tourniquet-related hypertension and short-term (3 days after operation) complications (nausea and vomiting, swelling, blister, wound infection) and long-term (3 months after operation) complications (joint instability, stiffness, nerve paralysis, pain) were recorded.Main Results: The expression of dystrophin in the rocuronium group was higher than that in group S after ischemia (P < 0.05). The concentration of MDA in the rocuronium 1.2 mg/kg group was lower at 30 min after reperfusion (P < 0.05). There was no significant difference in nNOS among groups at each time point (P > 0.05). The change of thigh girth was the smallest in the rocuronium 1.2 mg/kg group after operation (P< 0.05). The leaving bed time was significantly earlier after operation in the rocuronium group than that in group S (P < 0.05).Conclusion: Rocuronium can protect skeletal muscle from ischemia-reperfusion injury induced by tourniquet. The mechanism may be related to the fact that rocuronium can reduce the loss of dystrophin in skeletal muscle and have the effects of anti-oxidation and anti-stress.Trial Registration: The study was registered at http://www.chictr.org.cn (ChiCTR1800019221, registered on 2018– 10-31).Keywords: ischemia-reperfusion injury, rocuronium, dystrophin, TKA